Polybius, the Pontic Sea and socioenvironmental disaster’s semantics - Silva, Dyel (Revista Archai, 2025)
The ancient Pontic Sea, known nowadays as the Black Sea, is one of the most important in history. During the Hellenistic period, the argument that it would become a shallow swamp, due to its alluviation and people’s ignorance of this process, became well known. In proposing a dialogue between Ancient History and Environmental History, we depart from the recent concept of socioenvironmental disaster in order to bring it closer to the typology of disaster in Polybius’ Histories (c. 200 - c. 117 B.C.E.), and of his investigation of the Pontic Sea. Our aim is to understand the semantics of this experience and to reflect on the historicity of human awareness of its dependence on the environment. Accordingly, we focus our analysis on the language in which this experience is conceptualized insofar as human actions and the fate of the sea are temporally articulated by the author. Finally, we conclude that there are expressive similarities between the contemporary and ancient semantics of disaster, given that Polybius advocated a consistent human ethic of investigating so as to people better adapt themselves to the environment. We also hope this to be a suggestion to strengthen ties between Ancient History and Environmental History.